1999
DOI: 10.1007/s002210050630
|View full text |Cite
|
Sign up to set email alerts
|

Standing on a continuously moving platform: is body inertia counteracted or exploited?

Abstract: We describe the characteristics of displacement of the head and hip in normal young subjects standing on a moving platform undergoing continuous sinusoidal horizontal translation in the antero-posterior direction, at frequencies ranging from 0.1-1 Hz. The head, hip and malleolus were marked by light-emitting diodes (LEDs), and the displacement of each LED was quantified by (1) the measure of the shift during each cycle of translation, (2) the standard deviation (SD) of the path travelled during the whole trial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
80
1
11

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(105 citation statements)
references
References 15 publications
13
80
1
11
Order By: Relevance
“…Repeated balance challenges in healthy sober subjects usually introduce an adaptive process enabling them to handle the balance challenges more easily after a learning phase (Corna et al, 1999). However, as illustrated by the significant interaction between period and alcohol in the multivariate GLM ANOVA analysis for all recorded body positions, alcohol intoxication had a very strong and growing destabilizing influence on the ability to handle sustained balance perturbations.…”
Section: Time Varying Effects Of Alcohol Intoxication During Balance mentioning
confidence: 98%
“…Repeated balance challenges in healthy sober subjects usually introduce an adaptive process enabling them to handle the balance challenges more easily after a learning phase (Corna et al, 1999). However, as illustrated by the significant interaction between period and alcohol in the multivariate GLM ANOVA analysis for all recorded body positions, alcohol intoxication had a very strong and growing destabilizing influence on the ability to handle sustained balance perturbations.…”
Section: Time Varying Effects Of Alcohol Intoxication During Balance mentioning
confidence: 98%
“…The CoM diagrams in diverse cognitive conditions also were relatively negative due to the absence of the vision. Previous studies reported the importance of vision on balance control but some of them compared its role with other sources of information during the balance like interference with proprioception of the neck and leg muscles (Bove et al 2009, De Nunzio et al 2005) and velocity of the support movement (Corna et al 1999, Diener et al 1982). …”
Section: Discussionmentioning
confidence: 99%
“…Subjects can acquire sensory information and anticipate the postural disturbance associated with the floor oscillation, and can therefore easily improve postural stability [26][27][28][29] . The improvement is brought by the control of individual body segments with minimum postural muscle activity 30) . During the floor oscillations, postural control against anterior and posterior perturbations is the most important issue.…”
Section: Postural Control During Transient Floor Translationsmentioning
confidence: 99%